The reconciled life a critical theory of counseling - Olson, R. Paul (Peabody, MA Hendrickson, 2001)
Includes bibliographical references and index.
First published 1997
Keywords: Counselling -- religious aspects -- Christianity; Clinical psychology -- relation to Christian counselling